Development of Interactive Electronic Student Worksheets on Electromagnetic Induction Based on Scientific Approaches - Rita Asma; Asrial Asrial; Maison Maison (Postgraduate, University of Mataram, 2020)
This study aims to develop an interactive electronic student worksheet (eLKS) on electromagnetic induction material with a scientific approach using 3D PageFlip, Camtasia Studio 8, and Adobe Flash Professional CS6. The research design used is a research & development design with instructional design procedures that refer to the ADDIE stage as a fundamental process in developing learning resources. The revision process is carried out through formative revisions based on data obtained from an individual, small group, and field trials. The results of the validator assessment of the validity of electronic student worksheet products were analyzed with the Cohen's Kappa formula and obtained k = 1.00 (valid) for the material and k = 0.89 (valid) for the media. The results of the implementation to 177 students and Level 1 evaluations showed that students had a good perception of the content and the media of eLKS. They also perceive that they are involved or participate in learning using eLKS. Level 2 evaluation results that use the independent-sample t-test method to compare the average scores of students who learn using eLKS and who don't use eLKS, show that there are significant score differences for learning with eLKS (M = 73.87, SD = 22.56) and learning does not use eLKS (M = 27.73, SD = 15.51); t (54) = 10.51, p = 0.00 (two-tailed). The difference in the mean value of 46 (95% confidence level) is large (eta squared = 0.58).